Egg Production and Quality of Magelang Duck Fed Diets Containing Different Ratio of Omega 3 : Omega 6 and Organic Zn - A Darmawan; K G Wiryawan; . Sumiati (Faculty of Animal Science, Bogor Agricultural University, 2013)
The aims of this study were to determine the feeding effect of diets containing different ratio of ω-3 and ω-6 fatty acids and organic Zn on egg production and quality of Magelang duck. A total of 90 ducks of 20 weeks old were randomly divided into 18 experimental units by assigning a completely randomized design with 6 treatments and 3 replications. There were 6 dietary treatments, namely 1) ration without palm oil, fish oil and organic Zn with the ratio of ω-3 : ω-6 was 1: 5 (R0), 2) ration with the ratio of ω-3 : ω-6 was 1: 1.5 + 200 ppm organic Zn (R1), 3) ration with the ratio of ω-3 : ω-6 was 1: 3 + 200 ppm organic Zn (R2), 4) ration with the ratio of ω-3 : ω-6 was 1: 4.5 + 200 ppm organic Zn (R3), 5) ration with the ratio of ω-3 : ω-6 was 1: 6 + 200 ppm organic Zn (R4), 6) ration with the ratio of ω-3 : ω-6 was 1 : 7.5 + 200 ppm organic Zn (R5). Observation was carried out for 9 wk. The results showed that the ration containing the ratio of ω-3 : ω-6 = 1 : 3 and organic Zn (R2) produced significantly (P<0.05) the highest egg production and the lowest egg production was resulted by the dietary treatment without oil and organic Zn. Ration containing the ratio of ω-3 : ω-6 = 1: 3 and organic Zn (R2) significantly (P<0.05) decreased feed conversion ratio to the lowest value and it was significantly different as compared to R0 and R5. It can be concluded that feeding diet containing ω-3 and ω-6 with the ratio of 1:3 + 200 ppm organic Zn improves egg production without decreasing egg quality.